Anxiety during early pregnancy predicts postpartum weight retention in obese mothers. (25th May 2013) - Bogaerts, Annick F. L.; Van den, Bea R. H.; Witters, Ingrid; Devlieger, Roland
<x xml:space="preserve">Abstract</x> Objective We aimed to describe the weight status of obese mothers 6 months after delivery and examine its relationship to important sociodemographical, behavioral, and psychological variables. Design and Methods Postpartum data from an interventional trial in obese pregnant women (n = 197), conducted in three regional hospitals, between March 2008 and June 2012, were available from 150 mothers. Obesity was defined as body mass index (BMI) ≥ 29 kg/m2. Predictors were examined from the pregnancy and postpartum period. Descriptive statistics were performed and linear regression models constructed. Results Postpartum weight retention (PPWR) 6 months after delivery ranges from −17 to + 19 kg with a mean of −1.28 kg (SD 6.05). Thirty‐nine percent showed PPWR (>0 kg) and 13% of obese mothers reported a high PPWR (≥5 kg). Gestational weight gain (GWG) and psychological discomfort were significantly higher in obese mothers with PPWR compared to those with no or low PPWR. Mean duration of breastfeeding in this cohort of obese mothers was 9.5 weeks (SD 8.7), with 17.3% breastfeeding for at least 6 months. At 6 months after delivery, prepregnancy BMI (β = −0.283; P = 0.001), GWG (β = 0.337; P = 0.001), and maternal trait anxiety in the first trimester of pregnancy (β = 0.255; P = 0.001) were significantly associated with PPWR in obese mothers. Conclusion PPWR in obese mothers is associated with psychological discomfort during early pregnancy. Besides the importance of adequate prenatal weight management, focused psychological support should be an important cue to action in obese women, to prevent maternal obesity on the long run.